2011
DOI: 10.1007/s00421-011-1860-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological elevation of endogenous hormones results in superior strength training adaptation

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Rønnestad, B. R., Nygaard, H., Raastad, T. (2011) ABSTRACTThe purpose of this study was to determine the influence of transiently elevated endogenous hormone concentrations during exercise on strength training adaptations. Nine subjects performed four unilateral strength training session per week on the elbow flexors for 11 weeks. During two of the weekly sessions, leg exercises were performed to acutely increase the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 71 publications
4
53
0
2
Order By: Relevance
“…Consistent with previous findings for resistance exercise, serum T concentrations were significantly increased immediately following the kettlebell exercise bout. The magnitude of post exercise increase in T concentrations was similar to that found in some previous studies on free weight resistance exercise (Hansen et al, 2001;Linnamo et al, 2005;Ronnestad et al, 2011); however, the duration of the increase was shorter than found in some studies (Hansen et al, 2001;Kraemer et al, 1998). The cause of this shorter duration for the elevation in testosterone concentration is not known, but could be due, at least in part, to plasma volume shift.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous findings for resistance exercise, serum T concentrations were significantly increased immediately following the kettlebell exercise bout. The magnitude of post exercise increase in T concentrations was similar to that found in some previous studies on free weight resistance exercise (Hansen et al, 2001;Linnamo et al, 2005;Ronnestad et al, 2011); however, the duration of the increase was shorter than found in some studies (Hansen et al, 2001;Kraemer et al, 1998). The cause of this shorter duration for the elevation in testosterone concentration is not known, but could be due, at least in part, to plasma volume shift.…”
Section: Discussionsupporting
confidence: 88%
“…The neuromuscular adaptations to resistance training are modulated by the endocrine milieu and acute hormonal response to each exercise bout (Hansen, Kvorning, Kjaer, & Sjogaard, 2001;Kvorning, Andersen, Brixen, & Madsen, 2006;Ronnestad, Nygaard, & Raastad, 2011). Concentrations of circulating of testosterone, growth hormone, cortisol, and other hormones are increased in response to an acute bout of heavy resistance exercise (Kraemer, Noble, Clark, & Culver, 1987;Kraemer et al, 1998;Linnamo, Pakarinen, Komi, Kraemer, & Hakkinen, 2005;Smilios, Pilianidis, Karamouzis, & Tokmakidis, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was evident as a lack of effects on FNDC5 expression in both VL and BB and s-irisin. This may be due to a type II error, as even subtle changes in design of strength training protocols have previously been found to affect training-associated adaptations following upper body strength exercises (Rønnestad et al 2011). However, this study was performed on men, and its findings may not be relevant to women.…”
Section: Discussionmentioning
confidence: 99%
“…While engaging in physical competition often results in acute increases in testosterone in both competitors, the winners of male-male competition appear to have larger increases in testosterone across many taxa [107], including many, though not all, studies in humans [39]; this phenomenon is often called the 'Winner Effect' or 'WinnerChallenge Effect'. In humans and animal models, repeated acute increases in testosterone during physical activity have the potential to benefit muscle physiology [104,105,110] (though see [111,112], and the rebuttal [113]). In animal models, repeated winning during conflict can result in more aggressive strategies and the increased probability of winning future fights [107,114].…”
Section: (B) Testosterone and Dyadic Competitionmentioning
confidence: 99%